The tour guide to the monuments of socialism in Prague - Adámková, Lenka; Jarolímková, Liběna; Netková, Jarmila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
The bachelor thesis deals with the form of architecture in Czechoslovakia in the socialist era, ie. the years 1948 - 1989. It brings closer the historical background of particular decades, the prevailing architectural trends among the Czechoslovak architects and urbanism efforts which created current cities. It is applied specifically to Prague and it is dedicated to the most significant or controversial buildings, assessed in terms of architecture, importance or discussibility. Furthermore, this thesis proposes possible tour routes according to the territorial and thematic consistency and suggests potential clientele.
Vedoucí práce: Liběna Jarolímková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: cestovní ruch a regionální rozvoj [obor bakal. práce]; bakalářské práce; bachelor's theses